Fatigue Life Assessment Method for Prestressed Concrete Sleepers - You, Ruilin; Li, Dan; Ngamkhanong, Chayut; Janeliukstis, Rims; Kaewunruen, Sakdirat (Frontiers in Built Environment, 2017)
Concrete sleepers are one of the most important applications of a railway track system. Researchers have previously studied the impact load characteristics and ultimate load carrying capacity of a prestressed sleeper but research on the fatigue life of prestressed concrete sleepers is limited. Prestressed concrete sleeper fatigue damage is mainly due to the accumulation of defects, caused by the repeated load of wheel-rail interaction. Fatigue load, fatigue characteristics and the existing design methods of prestressed concrete sleeper are summarized in this paper. The commonly used fatigue assessment methods of concrete structures are also evaluated. Based on the results of former research result, this article presents a convenient fatigue life assessment method for a prestressed concrete sleeper, and contrasts with the test results. The insight information gained can be used to evaluate the service performance and predict the fatigue life of the concrete sleeper, as well providing design flexibility and broadening the design principle. The outcome of this study may also improve the rail track maintenance and inspection criteria, in order to establish an appropriate track condition monitoring network in practice.